Implementation of Pancasila Values in the Frame of Unity in Diversity in the Palembang City 11 Public High School Environment: Implementation of Pancasila Values in the Frame of Unity in Diversity in the Palembang City 11 Public High School Environment - Hani atul Mar’ah (LPPM Institut Studi Islam Sunan Doe, 2022)
The implementation of Pancasila values ​​has many positive impacts, especially for the next generation, in this case they are students. The aim of this study is to find out how the implementation of Pancasila values ​​in the Senior high school 11 Palembang city school environment. The research method used the observation method. The observation method was done by interviewing and observing the object directly. In addition to the observation method, this research also used the study literature method. The implementation of Pancasila values ​​observetion was Pancasila precepts 1 to 5. The results and conclusions of the research that has been conducted at Senior high sechool 11 Palembang city that the school had implemented Pancasila values ​​in the school environment. This is reflected in the process of learning and interaction between students that takes place in the school environment.